Description of the larva of the Caucasian species, Protonemura bifida Martynov (Plecoptera, Nemouridae) - Zhiltzova, Lidia A. (Illiesia, 2010)
Thirty five streams entering Kootenay Lake, British Columbia were sampled for stoneflies over a seven day period in late May and early June, 2010. The collections include 874 specimens and 34 species which increase the number of stonefly species reported for this area to 42, and many new locality records are added for British Columbia. Male and female specimens of Megaleuctra collected at two sites in the study area were determined as M. stigmata (Banks) which supports the synonymy of M. spectabilis Neave with this species.Samples were also taken from Summit Creek and the South Salmo River, two streams outside the Kootenay Lake basin for comparison. A checklist of 42 Plecoptera species reported for the Kootenay Lake drainage basin is presented and the first provincial records for Paraleuctra jewetti Nebeker & Gaufin and P. projecta (Frison) are given.
Keywords: entomologija; entomology; new species; vrbnice; Protonemura; larval description; Nemouridae; Caucasus; Plecoptera